"Reality check": supporting law student diversity and achievement through a novel model of support and assessment of academic literacy: student perceptions, retention and performance. Issue 3 (3rd July 2021) - Noakes, Sandra
ABSTRACT: Changes in the higher education sector globally have resulted in the transition from an elite to a mass model of education, encouraging the participation of students who have traditionally been underrepresented at university. Law schools in a number of countries face the dual pressures of an increasingly diverse student population, and the imperative to meet externally imposed accreditation requirements of the legal profession and the higher education regulation authorities. It appears that law schools could do more to support their students' academic literacy, and in particular their writing skills. At the Western Sydney University (WSU) law school the issue of a diverse student cohort and academically underprepared students has been addressed by the introduction of a novel model of support and assessment of students' academic literacy. This article examines the Academic Literacy Support (ALS) program at WSU law school, its function in terms of setting student expectations, motivating students to obtain support, and the impact on student retention, confidence and performance.